Transcriptional Organization and Regulation of a Polycistronic Cold Shock Operon in Sinorhizobium meliloti RM1021 Encoding Homologs of the Escherichia coli Major Cold Shock Gene cspA and Ribosomal Protein Gene rpsU - O'Connell, Kevin P. (American Society for Microbiology, 2000)
A homolog of the major eubacterial cold shock gene cspA was identified in Sinorhizobium meliloti RM1021 by luxAB reporter transposon mutagenesis. Here we further characterize the organization and regulation of this locus. DNA sequence analysis indicated that the locus includes three open reading frames (ORFs) encoding homologs corresponding to CspA, a novel 10.6-kDa polypeptide designated ORF2, and a homolog of the Escherichia coli ribosomal protein S21. Transcription analysis indicated that this locus produced two different-sized cspA-hybridizing transcripts upon cold shock, a 400-nucleotide (nt) RNA encoding cspA alone and a 1,000-nt transcript encoding cspA-ORF2-rpsU. The sizes of the transcripts agreed with the location of the transcription start site determined by primer extension and the locations of two putative transcriptional terminators. The promoter of the cspA-ORF2-rpsU locus had −10 and −35 elements similar to the E. coli ς(70) consensus promoter and, like the cspA locus of E. coli, included an AT-rich region upstream of the −35 hexamer. The promoter of the S. meliloti cspA locus was found to impart cold shock-induced mRNA accumulation. In addition, the 5′-untranslated region (5′ UTR) was found to increase the fold induction of cspA transcripts after cold shock and depressed the level of luxAB mRNA prior to cold shock, another feature similar to cspA regulation in E. coli. No “cold box” was identified upstream of the S. meliloti cspA gene, however, and there was no other obvious sequence identity between the S. meliloti 5′ UTR and that of E. coli. DNA hybridization analysis indicated that outside the cspA-ORF2-rpsU cold shock locus there are several additional cspA-like genes and a second rpsU homolog.